Promises and pitfalls of imaging the brain. (18th October 2018) - Baker, Chris
Chris Baker enjoys Russell Poldrack's clear-eyed account of attempts to decode brains scans. Chris Baker enjoys Russell Poldrack's clear-eyed account of attempts to decode brains scans.